PENGARUH ASEAN-INDIA FREE TRADE AGREEMENT (AIFTA) TERHADAP INDUSTRI PETROKIMIA INDONESIA PADA SEKTOR PERDAGANGAN - Puteri Dwi Lestari; Pazli Mahyudin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research examines the trade relations between Indonesia and India within the framework of AIFTA. Motivation ASEAN cooperation with India as there are market signals. India is the third economic power in Asia. India is the seventh largest trading partner for ASEAN. Therefore the Indian economy would greatly affect the economy of the member states of ASEAN. This research will look at how internasional trade between India and Indonesia before and after AIFTA implemented.This study used a qualitative research method. Data collect through the study of literature (Library Research). The scope of this research are used to clarify the effect of the Asean-India Free Trade Agreement For Petrochemical’s Industry in Indonesia on Trade Sector.The results showed that AIFTA distort Indonesia petrochemical industry in upstream and downstream aspects. Implementation of AIFTA triggered floods Indian origin imported plastics products at more competitive prices due to duty-free entry, so not only undermine the performance of the downstream plastics industry, but come to existence of the upstream industry. This is due the petrichemical industry between India and Indonesia is much different where the Indian petrochemical industry ia already integrated with a large production capacity while in Indonesia just the oppposite.Key word: Asean India Free Trade Agreement, International trade, Petrochemical Indutry, distortion